1996
DOI: 10.1164/ajrccm.154.5.8912741
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm strength in chronic obstructive pulmonary disease.

Abstract: The diaphragm is normally the main inspiratory muscle and diaphragm strength in chronic obstructive pulmonary disease (COPD) is therefore of interest. We assessed diaphragm strength in 20 patients with severe stable COPD (mean FEV1 0.61, mean thoracic gas volume [Vtg] 5.31) and seven normal control subjects, measuring both maximal sniff transdiaphragmatic pressure (sniff Pdi(max)) and twitch transdiaphragmatic pressure (Tw Pdi) elicited by cervical magnetic stimulation (CMS) of the phrenic nerve roots at FRC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
2
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(170 citation statements)
references
References 22 publications
6
151
2
11
Order By: Relevance
“…Although this level of respiratory muscle dysfunction may not be clinically relevant at rest, it could have significant clinical implications under certain circumstances, such as during an exacerbation or physical exercise. Importantly, our observations were consistent with previous reports, where in vivo respiratory muscle and diaphragm strength were also shown to be compromised [14,21,22]. In keeping with this, it has recently been proposed [23] that in severe COPD, several molecular mechanisms contribute to the aetiology of this respiratory muscle dysfunction, such as myosin loss [10,11], sarcomeric injury [24], oxidative stress [14] and alterations in cross-bridge cycling kinetics [8], resulting in reduced diaphragm isometric force.…”
Section: Discussionsupporting
confidence: 92%
“…Although this level of respiratory muscle dysfunction may not be clinically relevant at rest, it could have significant clinical implications under certain circumstances, such as during an exacerbation or physical exercise. Importantly, our observations were consistent with previous reports, where in vivo respiratory muscle and diaphragm strength were also shown to be compromised [14,21,22]. In keeping with this, it has recently been proposed [23] that in severe COPD, several molecular mechanisms contribute to the aetiology of this respiratory muscle dysfunction, such as myosin loss [10,11], sarcomeric injury [24], oxidative stress [14] and alterations in cross-bridge cycling kinetics [8], resulting in reduced diaphragm isometric force.…”
Section: Discussionsupporting
confidence: 92%
“…An index of inspiratory muscle strength was obtained by measuring Poes and Pdi during a maximal sniff [16].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…25,26 During exercise it has been shown that diaphragm work is increased in COPD and COPD patients use a larger proportion of the maximal inspiratory pressure (PI max) than healthy subjects. This pattern of breathing is closely related to the dyspnea sensation during exercise and might potentially induce respiratory muscle fatigue.…”
Section: 10mentioning
confidence: 99%
“…This pattern of breathing is closely related to the dyspnea sensation during exercise and might potentially induce respiratory muscle fatigue. 4,25,26 In an experiment, a meta-analysis including 32 random controlled trials on the effects of inspiratory muscle training (IMT) in COPD patients were performed. 27 In this study the effect size of each individual study was calculated by the difference between the means of the experimental and the control groups before and after the intervention divided by the average population standard deviation.…”
Section: 10mentioning
confidence: 99%